ANALISIS HARGA PANGAN POKOK DAN SALING KORELASINYA DI KABUPATEN ACEH BARAT - Aswin Nasution; Hafnidar Hafnidar (Jurnal Bisnis Tani, 2018)
Food is a human physiological need that occupies the first herarchy of basic human needs.In addition to its availability, the others important factors of food are price,rising food prices will potentially lead to social problems.This study was conducted to find outfluctuation of 19 staple food prices and mutual correlation between one another in West Aceh District.Staple food prices that experience significant fluctuations in the district of West Aceh in 017 aregarlic,Cayenne pepper,red chili pepper and beef.This price fluctuation is caused by the imbalance between the needs and supply, the price of staple foods that do not experience significant fluctuations are rice, sweet potatoes, sugar, sweet corn, soybeans and cassava.Between one staple food price and the others have a moderate to very strong correlation, positive and negative correlations. Sugar prices have almost no correlationwith other staple food so the price is stable relatively.